Monocots : systematics and evolution - Wilson, Karen L., 1950-; Morrison, David A., 1958- (CSIRO, 2000)
Monocots: Systematics and Evolution presents leading work from around the world on non-grass monocotyledons and includes reviews and current research into their comparative biology, phylogeny and classification. The papers are based on presentations at the Second International Conference on the Comparative Biology of the Monocotyledons, Monocots II, held in Sydney, Australia in late 1998. Many were subsequently updated or extended to take into account new information. All 72 papers have been peer-reviewed.